Structure of The Plankton Community in Tanjung Pasir Sea Waters, Tarakan City - M. Gandri Haryono; Dhimas Wiharyanto; Tuty Alawiyah; Cici Helmi (Sriwijaya Journal of Environment, 2023)
Tarakan City is a city that has potential natural resources to be developed. One of the areas in the town of Tarakan is Tanjung Pasir, where the residents live in the coastal area. This study aims to determine the quality of the waters of the dune by using the plankton community structure as a water bioindicator. As a research object, Plankton communities in Tanjung Pasir waters include abundance, diversity index, uniformity index, and dominance index. This study uses a quantitative descriptive method with the research location being carried out at two points, namely Station I in the mangrove area and Station II close to residential areas. Sampling was conducted every two days, 15 times out in the field. The types of phytoplankton found in five classes, namely Bacillariophyceae, Coscinodiscophyceae, Cyanophyceae, Mediophyceae, and Dinophycea lessons and zooplankton from Crustacea class at Station I and Station II. Station I and Station II were from classes. The most abundant types of phytoplankton are found in Bacillariophyceae and Dinophyceae because these two classes dominate all kinds of phytoplankton worldwide. The abundance value of phytoplankton at; Station I was 354 cells/l; at Station II, it was 202 cells/l. The abundance of zooplankton at; Station I was 40 ind/l, and at Station, II was 38 ind/l. The diversity index at the two stations is in the medium category, with the uniformity index being in the high uniformity category and the dominance index at each low. Based on the value of the plankton community structure, Tanjung Pasir waters are classified as lightly polluted. Environmental factors of Tanjung Pasir waters in Tarakan city include the physical and chemical characteristics of Station I and Station II, which are still suitable for the life of aquatic organisms.